(untitled) (Plant Tissue Culture and Biotechnology, 2015)
Lychnis cognate Maxim and Lychnis fulgens Fish. Ex Spreng are two valued ornamental plants in Korea. Soaking of seeds in GA3 solution remarkably promoted germination up to 60%, but the control (0 mg/l) was not effective (> 5%). To select an adequate temperature for seed germination, seeds, previously soaked in a 1000 mg/l GA3 for 24 hrs, were incubated at 15, 20, 25, and 30°C. Seed germination of over 20% was obtained at 15, 20, and 25°C, but only 10% at 30°C. These results indicate that the seeds of L. cognate and L. fulgens are in a such dormant state that they hardly germinate even by dormancy breaker (GA3) and low (15 ? 25°C) temperature treatment. The highest callus induction was observed in the leaf explants of the seedlings on MS containing specific concentrations of 3.0 mg/l BA and 1.0 mg/l NAA. The adventitious shoot was formed < 90% of calli on 1/2 WPM medium. The height of in vitro propagated plantlet was no different media used for regeneration. This in vitro propagation protocol should be useful for conservation of endangered and ornamental plant. Plant Tissue Cult. & Biotech. 25(1): 1-12, 2015 (June)